Effects of Inflation Expectations on Inflation - Richhild Moessner (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study the effects of professionals' survey-based inflation expectations on inflation for a large number of 36 OECD economies, using dynamic cross-country panel estimation of New-Keynesian Phillips curves. We find that inflation expectations have a significantly positive effect on inflation. We also find that the effect of inflation expectations on inflation is larger when inflation is higher. This suggests that second-round effects via the effects of higher inflation expectations on inflation are more relevant in a high-inflation environment.
Keywords: E52; E58; 330; inflation; inflation expectations; Phillips curve